The effects of grain processing method, wet and dry distiller’s grains with soluble and roughage level on performance and carcass characteristics of finishing cattle - May, Matthew Leonard (Kansas State University, 2008)
A series of five trials were conducted to evaluate grain processing, distiller's grains inclusion in finishing diets, interactions between distiller's grains and dry-rolled corn (DRC) or steam-flaked corn (SFC), efficacy of removing roughage in the presence of distiller's grains and the digestibility of distiller's grains in steam-flaked and dry-rolled corn diets. The first trial was designed to determine the optimum flake density of SFC in beef finishing diets. Diets consisted of corn flaked to densities of 360, 411, or 462 g/L. Observed improvements in mill production would support increasing flake density; however numerical decreases in animal performance offset economic benefits of increased productivity. The second trial was conducted to evaluate optimum levels of sorghum wet distiller's grains in finishing diets. Crossbred yearling steers were fed diets containing DRC or SFC and levels of distiller's grains were 0, 10, 20, or 30% of diet dry matter. Distiller's grains can effectively replaced a portion of the corn in finishing diets, but their nutritional value was greater in DRC diets than in SFC diets. In trial 3, crossbred heifers were fed diets containing SFC with 0% DDG and 15% corn silage (CS), 25% DDG and 15% CS, or 25% DDG and 5% CS. In trial 4, crossbreed heifers were fed diets similar containing DRC or SFC with 0% DDG and 15% CS, 25% DDG and 15% CS, or 25% DDG and 5% CS. Results indicate that roughage levels can be reduced in feedlot diets containing DDG with no adverse effects on performance or carcass quality. The fifth trial was a metabolism study conducted to evaluate the digestibility of DDG in beef cattle. Treatments consisted of DRC with 0% DDG, DRC with 25% DDG, SFC with 0% DDG, and SFC with 25% DDG. There were no significant grain processing by distiller's grain interactions observed in main effects. In conclusion optimum flake density was 360 g/L, feeding distiller's grains has a greater value in DRC diets vs. SFC diets, roughage level and type are important in formulating finishing diets, roughage can be reduced when feeding distiller's grains, and ruminal ammonia, and pH are decreased and ruminal lactate is increased when feeding DDG and SFC.
Keywords: beef; distiller's grains; corn; Agriculture, Animal Culture and Nutrition (0475)